Impartiality and the construction of trust in investor-state dispute settlement - Brekoulakis, Stavros (Institutional Knowledge at Singapore Management University, 2023)
This article analyses impartiality in investor-State dispute settlement (ISDS) by identifying the way that the parties’ trust in arbitrators is constructed. Drawing on the findings of a large-scale empirical project, it questions the applicability of an orthodox judicial doctrine of impartiality to ISDS on the grounds that trust in arbitrators is constructed on a fundamentally different basis from that of trust in judges. The primary feature of a judicial doctrine of impartiality is that trust is founded on an absolutist approach to impartiality which is intended to ensure that judges have no predispositions to parties. In contrast, trust in ISDS is founded on the method of party appointment which is based on a very different assumption—that arbitrators’ predispositions can be valuable and appropriate in the decision-making process. The empirical findings show that the parties’ choice of a predisposed arbitrator is generally considered compatible with the understanding of impartiality in ISDS. Accordingly, this article calls for a new, and contextualised, approach which better corresponds to the fundamental value of trust in ISDS.